Spectral and spatial characterisation of laser-driven positron beams. (18th October 2016) - Sarri, G; Warwick, J; Schumaker, W; Poder, K; Cole, J; Doria, D; Dzelzainis, T; Krushelnick, K; Kuschel, S; P D Mangles, S; Najmudin, Z; Romagnani, L; et al.
Abstract: The generation of high-quality relativistic positron beams is a central area of research in experimental physics, due to their potential relevance in a wide range of scientific and engineering areas, ranging from fundamental science to practical applications. There is now growing interest in developing hybrid machines that will combine plasma-based acceleration techniques with more conventional radio-frequency accelerators, in order to minimise the size and cost of these machines. Here we report on recent experiments on laser-driven generation of high-quality positron beams using a relatively low energy and potentially table-top laser system. The results obtained indicate that current technology allows to create, in a compact setup, positron beams suitable for injection in radio-frequency accelerators.